Interception of Criminal Prescription : A Comparative Study - Nazal, Duraid (Journal of Legal Sciences, 2023)
Criminal prescription is a legal idea that we find its applications in most laws, It means that a period of time has passed since the occurrence of the crime, which is called the prescription of the criminal case or the crime, or the lapse of a period of time since the issuance of a final judgment in the criminal case, and it is called the prescription of the penalty, the lapse of the prescribed period will result in the expiry of the criminal case in the first case, and the lapse of the penalty imposed in the second case. This system has been found since ancient times in the legislation of countries with their various legal and political systems because of its practical considerations, the most important of which is achieving legal stability that all legal systems aspire to. However, the Iraqi criminal legislation did not take this system as a general principle or rule and was limited to some applications in the special penal laws. However, it did not build the provisions related to the Interception of Criminal Prescription such as suspension and interruption and the consequences thereof represented in the lapse of the past period and the start of its calculation again - interruption -, Or it just results in the suspension of the period until its demise- suspension of the criminal prescription-.